Pengaruh Rasio Solvabilitas, Rasio Profitabilitas dan Kebijakan Dividen Terhadap Harga Saham - Kholilur Rachman; Ickhsanto Wahyudi (Jurnal Simki Economic, 2023)
his study aims to identify the relationship between the Solvability Ratio (DAR), Profitability Ratio (ROA) and Dividend Policy (DPR) on Stock Prices. This study utilizes information obtained from the consumer goods industry's financial reports published on the IDX, and uses a purposive sampling test method by fulfilling the exploration step. This study took observations over 3 years from 2019-2021 and obtained 75 data from 25 consumer goods industries. The research method used with the Statistical Package for the Social Sciences (SPSS) is of secondary data type. Obtained from the research shows that the Solvability Ratio (DAR) has no positive effect on Stock Prices, Profitability Ratio (ROA) has a partial and significant positive effect on Stock Prices and Dividend Policy (DPR) has no positive effect on Stock Prices.